Symptoms, causes, management and outcomes of hyponatraemia: a single centre study among hospitalised adult patients in Malaysia - Jing Wen Wong; Jun Hui Tan; Selavraju Navindran; Edmund Ong (Journal of Global Health Economics and Policy)
# Background